Diastereoselective Synthesis of Spirobarbiturate-Cyclopropanes through Organobase-Mediated Spirocyclopropanation of Barbiturate-Based Olefins with Benzyl Chlorides - Zhu, Yuanyuan; Zhao, Shuang; Zhang, Minli; Song, Xixi; Chang, Junbiao (Synthesis, 2019)
The organobase-mediated diastereoselective spirocyclopropanation of barbiturate-based olefins with 2,4-disubstituted benzyl chlorides has been developed. The reactions were carried out efficiently to afford the desired spirobarbiturate-cyclopropanes in up to 95% yield with more than 20:1 dr in favor of anti-isomers. In order to extend synthetic utility of the spiro-products, a Lewis acid induced cyclopropane-ring-expansion isomerization was also demonstrated.
Keywords: spirobarbiturate-cyclopropane; spirocyclopropanation; barbiturate-based olefin; benzyl chloride; diastereoselective; synthetic methodology; organobase